(3eSFhdjI GdHfc Yf aMU GdeSJfOGJ ai GdGYJeGO GdeSJfOi (B/ s - (3YUGe aGjO eMeOs; (3eMeO HgLJ bGjO s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2007)
(3fdNU ef GdHMK Gdi Gfg dJaGOi hbhY GdeSFhdjI Yf YedjI GdaMU jLH GdGgJeGe HGdYfUQ GdHTQi GdbGFe HGdaMU ef MjK GfJbGFg hJOQjHg ai GdOGNd hGdNGQL heOI g HGdeQGLY hGdOhQjGJ GddGReI hGdGLgRI GdMOjKI cGdMGSHGJ ddbjGe HGdaMU ai GdeOI GdebQQI hHGdeSJhi GdOhdi GdeWdhH(B.(3hjLH Ydi GdHfc GdaGMU GdGdJRGe HGdJYdjeGJ GdUGOQI ef GdYejd MQajG hYOe GdQchf Gdi Gf GdbhGYO GdOhdjI GYaJg ef GdeSFhdjI Yf GdZT hGdJRhjQ GdMGOKjf ai GdeSJfOGJs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdJLGQj, (B2007s
(3jTJed Ydi EQLGYGJ HHdjhLQGajI(B: (3UaMI (B569-590s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdJLGQjs; (3GdbGfhf GdJLGQjs; (3GdGYJeGO GdeSJfOis; (3aMU GdeSJfOGJs; (3eSFhdjI GdHfcs; (3GdJhbjY GdGdcJQhfis; (3GdSajfIs; (3SfO GdTMfs; (3hKjbI GdJCejfs; (3GdJQcs; (3GdHfc GdeDjOs; (3GdJLGQI GdGdcJQhfjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdJLGQjs